Effects of microcystin-LR on Saccharomyces cerevisiae growth, oxidative stress and apoptosis - Valério, Elisabete (2015)
Microcystins (MC) are cyanotoxins occurring globally, known for causing acute hepatotoxicity in humans/animals, tumor promotion in animals and potential carcinogenicity. The mechanism of MC toxicity is considered a multi-pathway process involving the inhibition of protein phosphatases PP1/PP2A and the production of reactive oxygen species (ROS). However, their mechanism of action is not fully characterized, thus hampering the complete hazard identification. In this study, we evaluated the effect of several microcystin-LR concentrations on the growth, ROS levels, antioxidant system response and apoptosis induction on Saccharomyces cerevisiae. Our results showed that the growth of S. cerevisiae was not inhibited when compared to control cells. However, the staining of cells with DHR123 and DHE revealed an intracellular increase of the ROS levels. This ROS increase resulted in an augment of catalase activity and inhibition of SOD. All these facts suggest that hydrogen peroxide was the main ROS induced by MCLR. Signs of apoptosis were also detected in the cells exposed to toxin. Our results show that S. cerevisiae VL3 displays MCLR toxicity effects known to occur in higher eukaryotes and confirmed that it can be a simple and good model to help further in the elucidation of MCLR molecular mechanisms of toxicity.